The biochemical genetics of certain structural genes of the regulation enzymic function 3-deoxy-D-arabino-heptulosonate 7-Phosphate synthetase - D. M. Halsall; C. H. Doy (Fungal Genetics Reports, 1967)
Regulation of DAHP synthetase